MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN SAINS KONSEP KEMAGNETAN MELALUI MODEL INKUIRI - Payu, Citron S (Jurnal Pelangi Ilmu, 2012)
Improving Student Results At Science Learning Magnetism Concept Through Model Inquiri in Class V Elementary School I Kaliyoso Kecamatan Bongomeme. About problem in this research (a) is model inquiri learning on magnetism concept can increase student studying result, (b), how student activity on inquiri learning, to reach good result, notably on magnetism concept at class V SDN 1 Kaliyoso Kecamatan Bongomeme there is even that as aim in obevational it, ti increase studying result and student activity via inkuiri learning one that as sample in observational it is student class V total one 28 person, 16 daughters and 12 son. This observational method utilize action research method brazes (PTK). Via preparation phase/observation, action performing phase, watch and evaluation what do happen deep 2 cycles and its result be described through phase analisis datas. Action observational result ones at analisis bases cycle 1 and 2 become step-ups namely of 46,4% gets one assesses to be more than 65 and absorbing powers 65 worked up as 92% by absorbing powers 66% thus can at concludes that inquiri Learningcan increase student studying result.